Vreme i gramatička kategoria vremena u sakralnom stilu - Bajić, Ružica S. (Stylistyka, 2021)
The aim of this paper is to describe the use of some Serbian tenses in sacral style (na- mely, in praying discourse), with regard to the special meaning of time in the Orthodox Church (e.g. that which emphasizes the eternity). The materiał we used was an Orthodox prayerbook. The project proved to be laborious; firstly because of the lack of research in sacral styles in modem linguistics and modem languages in generał, and secondly, because of vaguely-defined verb-tense concepts in Serbian linguistics.The main conclusion is that almost all tenses, especially most uses of the present and two past tenses (preterite and aorist) - serve exactly to emphasize the eternity. We have termed that stylistic characteristic svevremenost (in Serbian). The past tenses realize that characteristic by reminding us of some events from the Gospel. The present and the other uses of aorist, as well as the futurę tense, possess this main characteristic, as well; but to a lower extent. Namely, in the statements where the specified tense-uses appear, the wri- ter/reader speaks mostly about himself, not about God and some Church truths which are always valid - without either the beginning or the end. Furthermore, no matter how long one reads (speaks) these prayers (it is supposed that every Orthodox Christian reads them every day) - there will be the end to it, i.e. the end of everyone’s earthly life. The main functions of the Church language connected to the examined verb-tense uses are performative (present is used in many performative statements, which we also find as one of the characteristics of praying discourse), function of reminding us, and recording facts.